Factors Influencing the Incidence of Dengue Haemorrhagic Fever - Trijati Puspita Lestari; Siti Sholikhah; Nurul Hikmatul Qowi (Universitas Airlangga, 2019)
Background: Dengue Hemorrhagic Fever (DHF) is a contagious disease that is still a community problem in Indonesia. The purpose of this study was to analyze the factors related to the incidence of dengue fever in Deket village.Method: This study was an observational analytical study with a case control design. The data that was collected used interviews and questionnaires. The sample consisted of 39 for the case group and 39 for the control group. The variables used were 3M behavior (covering the water container, draining the water container, burying unused things) and the incidence of DHF. This study used the Chi-square test.Result: The results showed that there was a relationship between the habitual draining of the water reservoirs with dengue fever, where p=0.000 (p<0.005). There was a relationship between the habit of closing the water reservoirs with dengue fever; p=0.000 (p<0.005). There was a relationship between the habits of thrift burial with dengue hemorrhagic fever; p=0.000 (p<0.005).Conclusion: Based on these results, it is expected that the health cadres should control the implementation of 3M in the community.